Deepening regional economic cooperation between Fujian and Taiwan under the belt and road background based on regional spatial structure theory. Issue 6 (3rd October 2017) - Luo, Xing-Peng; Zhang, Xiang-Qian
Abstract: Based on regional spatial structure theory, this paper analyzed the mechanism of further regional economic cooperation between Fujian and Taiwan under the Belt and Road background. Then countermeasures and suggestions were put forward, including cooperation on agriculture, infrastructure, talent and industrial between Fujian and Taiwan.